Impact of the 2014 coinsurance rate revision for the elderly on healthcare resource utilization in Japan - Takumi Nishi; Toshiki Maeda; Susumu Katsuki; Akira Babazono (Health Economics Review, 2021)
Background: Cost sharing, including copayment and coinsurance, is often used to contain medical expenditure by decreasing unnecessary or excessive use of healthcare resources. Previous studies in Japan have reported the effects of a coinsurance rate reduction for healthcare from 30 to 10% on the demand for healthcare among 70-74-year-old individuals. However, the coinsurance rate for this age group has recently increased from 10 to 20%. This study aimed to estimate the economic impact of coinsurance rate revision on healthcare resource utilization. Methods: We collected claims data from beneficiaries of the municipality National Health Insurance and the Japanese Health Insurance Association in Fukuoka Prefecture. We categorized subjects born between March 2, 1944 and April 1, 1944 into the 20% coinsurance rate reduction group and those born between April 2, 1944 and May 1, 1944 into the 10% reduction group. An interrupted time-series analysis for multiple groups was employed to compare healthcare resource utilization trends before and after coinsurance rate reduction at 70 years. Results: The 10% coinsurance rate reduction led to a significant increase in healthcare expenditure for outpatient care. The 20% reduction group showed a significantly sharper increase in healthcare expenditure for outpatient care than the 10% reduction group. Similarly, the 10% coinsurance group significantly increased in the number of ambulatory visits. The 20% coinsurance rate reduction group had more frequent ambulatory care visits than the 10% reduction group. Conclusions: These results suggest that increasing the coinsurance rate among the elderly would reduce outpatient healthcare resource utilization; however, it would not necessarily reduce overall healthcare resource utilization.
Keywords: 330; Elderly; Health; Health insurance; Medical care; Public health